The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1177/0013164406288158
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Generalization Study on the Survey of Perceived Organizational Support

Abstract: The Survey of Perceived Organizational Support (SPOS) is a unidimensional measure of the general belief held by an employee that the organization is committed to him or her, values his or her continued membership, and is generally concerned about the employee's well-being. In the interest of efficiency, researchers are often compelled to use a minimum number of SPOS items in their studies. This study reports on a reliability generalization across 62 published studies using the SPOS. Findings suggest that numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 61 publications
0
35
0
2
Order By: Relevance
“…On this basis alone, one might recommend against using the three-item version when the eight-item version and the 16-item version perform better. This adds clarification to the statement by Rhoades and Eisenberger (2002) that 'the use of shorter versions does not appear problematic' (p. 699) and affirms a recommended caution with use of an extreme reduction in the number of SPOS items (Hellman, Fuqua & Worley, 2006). Table 2 reveal several interesting coefficients relative to answering the question of whether or not the versions are interchangeable.…”
Section: Discussionmentioning
confidence: 51%
“…On this basis alone, one might recommend against using the three-item version when the eight-item version and the 16-item version perform better. This adds clarification to the statement by Rhoades and Eisenberger (2002) that 'the use of shorter versions does not appear problematic' (p. 699) and affirms a recommended caution with use of an extreme reduction in the number of SPOS items (Hellman, Fuqua & Worley, 2006). Table 2 reveal several interesting coefficients relative to answering the question of whether or not the versions are interchangeable.…”
Section: Discussionmentioning
confidence: 51%
“…Supervisors' perceptions of organizational support were assessed using eight items that loaded highly on the Survey of Perceived Organizational Support (Eisenberger et al, ). Sample items were “[Name of the organization] really cares about me” and “[Name of the organization] shows very little concern for me (Reversed scored).” Prior research has consistently reported unidimensionality and high construct and predictive validity of versions of the survey of this length (Eisenberger & Stinglhamber, ; Hellman, Fuqua, & Worley, ; Rhoades & Eisenberger, ).…”
Section: Methodsmentioning
confidence: 98%
“…POS is defined as "global beliefs [that employees develop] concerning the extent to which the organization values their contributions and cares about their well being" (Rhoades & Eisenberger, 2002, p. 698 A meta-analysis of 70 empirical studies indicated that POS correlated with outcomes like performance, organizational commitment, and job satisfaction (Hellman, Fuqua, & Worley, 2006;Rhoades & Eisenberger, 2002). Antecedents linked to POS include fairness of treatment, support from organizational representatives, and human resource practices such as job security, autonomy, and participation in decision making (Eisenberger, Jones, Aselage, & Sucharski, 2004).…”
mentioning
confidence: 99%